Pemberian Izin Poligami Oleh Pengadilan Agama Di Indonesia - Fitri Rafianti (DE LEGA LATA: JURNAL ILMU HUKUM, 2019)
Polygamy is an inexhaustible problem for discussing the rise of classical fiqh law that seems to give an opportunity to a husband in polygamy, shifts to the rules and laws of state products that not only limit and complicate, but even prohibit and categorize a problem around family law as an illegal act. On the other hand, there is an arbitrary understanding of polygamy in Islamic Family Law in Indonesia. The nature of polygamy that develops in society that does not benefit women, therefore, from the issue of polygamy and its relation to institutionalization of law it becomes important to work out that individual civilization rules have entered the realm of public law, as one of the images dynamized in Islamic law This research is a normative juridical approach that is carried out by analyzing the problems that exist in this study through approaches to legal principles, as well as referring to legal norms contained in the laws and regulations relating to the title of this research.